Analisis Variasi Penggunaan Busi pada Sepeda Motor Yamaha Vixion Tahun 2015 Terhadap Daya, Torsi dan Emisi Gas Buang - Adriansyah Prasetiyo; Rifdarmon Rifdarmon (AEEJ : Journal of Automotive Engineering and Vocational Education, 2020)
This study aims to determine the effect of the use of variations of spark plugs on power, torque and exhaust emissions produced by Yamaha Vixion motorcycles in 2015. This study uses an experimental method with three variations of spark plugs. The results of research on nickel spark plugs obtained a maximum power of 12.7 Kw, a maximum torque of 11.14 N.m and exhaust gas emissions with CO levels of 4.24%, CO2 9.03%, HC 1214ppm. In platinum spark plugs there is an increase in power of 1.55%, torque of 0.89% torque and exhaust emissions with levels of 5.18% CO, 9.2% CO2, HC 1134ppm. Furthermore, iridium spark plugs have an increase in power of 4.5%, a torque of 3.47% and exhaust gas emissions with CO levels of 5.27%, CO2 9.6%, HC 1293ppm. That is, there is an influence from the use of variations of spark plugs on power, torque and exhaust emissions on Yamaha Vixion motorcycles in 2015. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan variasi busi terhadap daya, torsi dan emisi gas buang yang dihasilkan oleh sepeda motor Yamaha Vixion tahun 2015. Penelitian ini menggunakan metode eksperimen dengan tiga variasi busi. Hasil penelitian pada busi nikel didapatkan daya maksimal sebesar 12,7Kw, torsi maksimal sebesar 11,14 N.m dan emisi gas buang dengan kadar CO 4,24%, CO2 9,03%, HC 1214ppm. Pada busi platinum terdapat peningkatan daya sebesar 1,55%, torsi torsi 0,89% dan emisi gas buang dengan kadar CO 5,18%, CO2 9,2%, HC 1134ppm. Selanjutnya, pada busi iridium terdapat peningkatan daya sebesar 4,5%, torsi sebesar 3,47% dan emisi gas buang dengan kadar CO 5,27%, CO2 9,6%, HC 1293ppm. Artinya, terdapat pengaruh dari penggunaan variasi busi terhadap daya, torsi dan emisi gas buang pada sepeda motor Yamaha Vixion tahun 2015.